Nanny McPhee returns [videorecording (DVD)] - Howard, James Newton (Universal Studios Home Entertainment, 2010)
When Nanny McPhee appears at the farmhouse door of a busy young mother Isabel Green, she discovers that Mrs. Green's children are in an all-out household war with their two spoiled city cousins. Relying on everything from a flying motorcycle and a statue that comes to life to a tree-climbing piglet and an elephant that turns up in the oddest places, Nanny McPhee uses her magic to show the children five valuable lessons, the most important of which is how to get along.